Extraction, characterization and purification of flavonoids from filicophytes - Jarial, Rini (2017)
Plants are rich source of phytochemicals (flavonoids, terpenoids, alkaloids, phenols). These natural products have played a key role in pharma research, as many medicines are either natural products or derivatives. The present study is the exploration of selected ferns (Drynaria rigidula, Chelianthes tenuifolia, Asplenium nidus, Dipteris conjugata and Antrophyum callifolium) as a new candidate of natural compounds. This was done through a series of plant extraction, characterization and purification protocols. The methanolic fern-extracts (MFEs) from all five ferns were subjected to determine total phenolic content (TPC), total flavonoid content (TFC), antibacterial and antioxidant activities. TPC was determined following the Folin-Ciocalteu colorimetric method and TFC was determined using aluminium chloride colorimetric assay. Highest amount of TFC was noted in C. tenuifolia whereas best TPC was in D. rigidula. The MFEs of these ferns were assessed for antibacterial and antifungal activities by measuring inhibition zones against a panel of pathogenic bacterial and fungal strains using agar well diffusion method. The C. tenuifolia showed maximum inhibition zone against Staphylococcus aureus (26 mm). Out of all ferns, C. tenuifolia showed a significant antioxidative activity in vitro i.e. 2, 2-Diphenyl-1-Picrylhydrazyl (DPPH) radical scavenging potential of C. tenuifolia (MFE) with IC50 value of 50.37 mM. However, for human hepatoma HepG2 and human carcinoma HeLa cells C. tenuifolia (MFE) exhibited high anticancer activity using 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-Diphenyltetrazolium Bromide (MTT) assay than others ferns. The data revealed that MFE of C. tenuifolia had higher antioxidant and antibacterial activities that might be due to the polyphenols present in the crude extract. Among the five ferns we selected the best fern (C. tenuifolia) for purification of flavonoids. Two flavonoids were identified as rutin (2.8 mg) and quercetin (3.34 mg). The MIC values of purified flavonoids were 2.25 and 0.45 μg/ml against S. aureus and Enterobacter sp., respectively. Rutin and quercetin showed significant in vitro antioxidant activity, the scavenging potential of quercetin (86.1%) was higher than that of rutin (73.2%) were measured against stable, non –biological radicals such as DPPH. However, for human hepatoma HepG2 and human carcinoma HeLa cells, quercetin (80.91 ± 1.93) exhibited high anticancer activity than rutin (11.10 ± 2.10). The results suggested that MFE of C. tenuifolia could potentially be employed in traditional medicine as they are rich in compounds with antioxidant, antimicrobial and anticancer properties.